The Use of Construction Management Information Systems: Efforts to Improve the Service Quality for Building Permit in Polewali Mandar Regency - Herlina Sakawati; sulmiah sulmiah; Amelia Reskiani Rahmat; Widyawati Widyawati (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2023)
Public service innovation offers the use of technology as an effort to improve service quality. The One-Stop Integrated Investment and Licensing Service of Polewali Mandar Regency has currently used the Building Management Information System (SIMBG) application to provide convenience in building permit services, but the implementation of the application has not been implemented optimally in providing services to the community. Through qualitative methods, this study aims to analyze the improvement in the quality of service for building permits/building applications in Polewali Mandar Regency, through the use of the SIMBG Building Management Information System, which has been in use since 2018. The data in this study were predominantly sourced from interviews. , which is also strengthened by the results of observation and documentation. Each data obtained before it reaches the analysis stage, is carried out by a reduction process, and triangulated to test the validity of the data. After the data is considered valid, the data is analyzed and presented in the form of narratives and pictures and conclusions are made. The results of data analysis show that the use of SIMBG has not been optimal in increasing the quality of building permit services. This is influenced by poor network quality which then also has an impact on employee performance in providing services. Through SIMBG, SIMBG employees and operators canimprove their skills and abilities in using technology to provide services.